2010
DOI: 10.1063/1.3501123
|View full text |Cite
|
Sign up to set email alerts
|

Diluted manganese on the bond-centered site in germanium

Abstract: The functional properties of Mn-doped Ge depend to large extent on the lattice location of the Mn impurities. Here, we present a lattice location study of implanted diluted Mn by means of electron emission channeling. Surprisingly, in addition to the expected substitutional lattice position, a large fraction of the Mn impurities occupies the bond-centered site. Corroborated by ab initio calculations, the bond-centered Mn is related to Mn-vacancy complexes. These unexpected results call for a reassessment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Although previous EC results have indicated that several impurities in Ge not only occupy the substitutional site but also other high-symmetry sites, such as the BC site and the T site, [8][9][10][11][12] an excellent fit to the presented data in Fig. 2 (a-d) which is consistent in all four directions, is obtained by assuming that all As atoms occupy an undisplaced substitutional site.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Although previous EC results have indicated that several impurities in Ge not only occupy the substitutional site but also other high-symmetry sites, such as the BC site and the T site, [8][9][10][11][12] an excellent fit to the presented data in Fig. 2 (a-d) which is consistent in all four directions, is obtained by assuming that all As atoms occupy an undisplaced substitutional site.…”
Section: Resultssupporting
confidence: 70%
“…It was shown in a direct way that this donor occupies an undisplaced substitutional site in the diamond lattice structure of Ge. Contrary to earlier EC experiments, where several impurities were found to occupy interstitial sites as well as substitutional sites, [8][9][10][11][12] no As atoms were found on any interstitial site or on a displaced substitutional site.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This has been suggested, e.g., for several TMs in Ge. 35,36 Because this ideal configuration is not observed for 3d TMs in Si, it has been proposed that other multivacancy complexes could be involved. In particular, the TM may occupy displaced BC sites inside hexavacancy rings to satisfy the fourfold coordination of neighbor Si host atoms.…”
Section: B Near-bc Sitesmentioning
confidence: 99%
“…[15] More recently, spectroscopic studies of Ge:Mn have been performed aiming at elucidating the geometry of Mn-related defects in Ge. As suggested by Decoster et al [16] the magnetic behavior of a transition metal impurity strongly depends on its location in the lattice.…”
Section: Introductionmentioning
confidence: 99%